Dany jest trójmian kwadratowy w postaci kanonicznej. Sprowadż go do postaci iloczynowej:
a) f(x) = 2(x+1)² - 8
b) f(x)= - (x+5)² +9
c) f(x)= - ⅓(x-3)² +3
f(x)= (x+8)² -25
Rozwiąż równania :
a) x² + 3x-18= (2x-6) (2x-1)
b)2x²+9x-5= (2x-1)²
c)(4x-5)²= 4x²- 9x +5
d)3(x+1)(x-2)= 2x²-x-7

2

Odpowiedzi

2009-11-29T23:46:41+01:00
A) f(x) = 2(x+1)² - 8
f(x)=2x²+4x-6/:2
f(x)=x²+2x-3
p. iloczynowa f(x)=(x+3)(x-1)
b) f(x)= - (x+5)² +9
f(x)= -x²-10x-16/:(-1)
f(x)= (x+2)(x+5)
c) f(x)= - ⅓(x-3)² +3
f(x)= - ⅓x²+2x
f(x)= - x(⅓x-2)
d)f(x)=(x+8)² -25
f(x)=x²+16x+39
Δ=b²-4ac=256-156=100 √Δ=10
x₁=(-b-√Δ)/2a=-13
x₂=(-b+√Δ)/2a=-3
zad.2Rozwiąż równania :
a) x² + 3x-18= (2x-6) (2x-1)
x² + 3x-18= 4x²-14x+6
3x²-17x+24=0
Δ=b²-4ac=289-288=1 √Δ=1
x₁=(-b-√Δ)/2a=8/3
x₂=(-b+√Δ)/2a=3
b)2x²+9x-5= (2x-1)²
-13x=6/:(-13)
x=-6/13
c)(4x-5)²= 4x²- 9x +5
49x=-20/:49
x=-20/49
d)3(x+1)(x-2)= 2x²-x-7
x²-2x+1=0
(x-1)²=0
x-1=0
x=1
2009-11-30T00:06:08+01:00
A)2(x+1)²-8= 2(x²+2x+1)-8= 2x²+4x+2-8= 2x²+4x-6= x²+2x-3
Δ=b²-4ac= 4+ 12=16 √Δ=4 x1=-2-4/2= -3 x2= -2+4/2 = 1
(x-x1)(x-x2)= (x+3)(x-1)

b)-(x+5)²+9= -(x²+10x+25)+9=- x²-10x-25+9= -x²-10x-16
Δ=b²-4ac = 100 - 4(-1x-16) =100-64=36 √Δ=6
x1= 10-6/-2= -2 x2= 10+6/-2= -8
(x-x1)(x-x2)=(x=2)(x+8)
1 5 1